Towed array beamforming during ship's maneuvering - Felisberto, P. (2014)
Towed hydrophone arrays are commonly used for determining the spatial characteristics of the underwater acoustic field. The assumption that the hydrophones lie in a straight and horizontal line is often made when beamforming the hydrophone outputs. However, due to tow vessel motion, ocean swells and currents the array adopts a nonlinear shape and the beamformer output is degraded. To estimate the positions of the hydrophones an array was instrumented with a set of positioning sensors: compasses, tiltmeters, accelerometers and pressure gauges. The authors present the array deformations recorded at sea when the tow vessel is turning and along straight-line tracks. The influence of the observed deformations on the performance of the conventional beamformer output is discussed and illustrated with simulated and real acoustic data